MBSE delivers significant return on investment in evolutionary development of complex SoS. Issue 6 (21st July 2021) - Rogers, Edward B.; Mitchell, Steven W.
Abstract: The Submarine Warfare Federated Tactical Systems (SWFTS) is a rapidly evolving combat system of systems (SoS) product family. Managing the annual baseline updates requires processing thousands of baseline change requests, then coordinating and verifying their implementation. The complexity of this effort, which involves well over ten million source‐lines‐of‐code (SLOC) as well as Commercial‐Off‐the‐Shelf (COTS) and military‐unique hardware, is compounded by being deployed in ten variants. After a feasibility study in 2010 the SWFTS systems engineering and integration program started a transition from traditional requirements database and document‐centric systems engineering (DCSE) to a model‐based systems engineering (MBSE) process. At that time there was little solid evidence in the literature for a positive Return on Investment (ROI) for moving from DCSE to MBSE. Applying MBSE to this program has resulted in measurable monetary and operational benefits. We 1) summarize the DCSE to MBSE transition, 2) describe the accomplishments and observations to date, 3) define the metrics collected, and 4) quantify the achieved ROI. Background on the systems engineering and integration (SE&I) process and an apples‐to‐apples comparison of SE quality and efficiency are provided. The raw SE&I efficiencies of the DCSE and MBSE approaches are documented, along with conclusions showing that the MBSE approach delivers a positive ROI through higher quality SE products at significantly less cost‐per‐change, enables managing more baselines and SoS complexity using constant resources, and reduces the cost of the downstream integration effort.